Community Translation: Translation as a social activity and its possible consequences in the advent of Web 2.0 and beyond - O’Hagan, Minako (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
This introduction to the 10th issue of Linguistica Antverpiensia New Series – Themes in translation Studies (LANS-TTS) begins by discussing the central concept of community translation, highlighting its terminological ambiguity. This is in part due to the already well-established field of community interpreting where the term is often used to mean the written translation of public information for immigrants. It is also an indication of the terminological instability typical of an emerging paradigm. For example, community translation is used more or less synonymously with such terms as translation crowdsourcing, user-generated translation and collaborative translation. The meaning of the term as we discuss in this issue can be best specified when the concept is anchored in the context of Web 2.0 (second generation web-technologies). This in turn acknowledges its intrinsic tie to online communities and directs us to new dynamics resulting from general Internet users acting as translators. While participants in community translation are not necessarily all unpaid, untrained volunteers community translation is used by some organisations as a mechanism to obtain free translations by going outside the professional translation sphere. To this end the ethical question of profit-making enterprises accessing free labour on the pretext of openness and sharing remains. That said, the author believes community translation is far more than a dilettante, anti-professional movement. Building on the emerging picture from the contributions in this volume, the author suggests some of the future directions that research on community translation might take, emphasising the need to reflect on the current translation practices and be open to the new developments and opportunities arising from the free and social Internet.